2011
DOI: 10.1093/toxsci/kfr125
|View full text |Cite
|
Sign up to set email alerts
|

Blood Gene Expression Profiling Detects Silica Exposure and Toxicity

Abstract: Blood gene expression profiling was investigated as a minimally invasive surrogate approach to detect silica exposure and resulting pulmonary toxicity. Rats were exposed by inhalation to crystalline silica (15 mg/m³, 6 h/day, 5 days), and pulmonary damage and blood gene expression profiles were determined after latency periods (0-16 weeks). Silica exposure resulted in pulmonary toxicity as evidenced by histological and biochemical changes in the lungs. The number of significantly differentially expressed genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 51 publications
5
62
1
Order By: Relevance
“…Elevated levels of macrophage inflammatory protein (MIP)-2 [a potent chemokine for PMN (Wolpe et al, 1989)] have been found in BALF of rats following a 5-day inhalation exposure to a-quartz at 15 mg/m 3 , but they returned to control level before they increased progressively later (Sellamuthu et al, 2011). In relation to this, macrophages, monocytes and dendritic cells (DCs) of different origins exposed to a-quartz in vitro have been demonstrated to enhance mRNA expression or protein production of IL-8 [a potent chemokine for PMN (Allen & Kurdowska, 2014)] (Xu et al, 2003) and MIP-2 (Rao et al, 2004;Sayes et al, 2007), although Zeidler et al (2003) failed to demonstrate enhanced MIP-2 production in murine bronchoalveolar lavage cells exposed to a-quartz.…”
Section: Inflammatory Reactions and Fibrosis In The Lungmentioning
confidence: 99%
“…Elevated levels of macrophage inflammatory protein (MIP)-2 [a potent chemokine for PMN (Wolpe et al, 1989)] have been found in BALF of rats following a 5-day inhalation exposure to a-quartz at 15 mg/m 3 , but they returned to control level before they increased progressively later (Sellamuthu et al, 2011). In relation to this, macrophages, monocytes and dendritic cells (DCs) of different origins exposed to a-quartz in vitro have been demonstrated to enhance mRNA expression or protein production of IL-8 [a potent chemokine for PMN (Allen & Kurdowska, 2014)] (Xu et al, 2003) and MIP-2 (Rao et al, 2004;Sayes et al, 2007), although Zeidler et al (2003) failed to demonstrate enhanced MIP-2 production in murine bronchoalveolar lavage cells exposed to a-quartz.…”
Section: Inflammatory Reactions and Fibrosis In The Lungmentioning
confidence: 99%
“…However, it is also important to examine chronic responses, such as persistent inflammation. There are reports [10,11] that exposure to crystalline silica, a material known to have high toxicity, induced the onset of pulmonary inflammation after a certain observation time and more severe inflammation in the chronic phase. Considering the pulmonary toxicity of nanomaterials, it is important to evaluate the endpoints, such as inflammation and fibrosis, not only in the acute but also in the chronic phase.…”
Section: Introductionmentioning
confidence: 99%
“…(8) The system required a minimum of operator intervention over an exposure period. Following testing, this method for exposing small animals to various constant concentrations of SiO2 has proven to be very successful for researchers at NIOSH (Sellamuthu et al, 2011(Sellamuthu et al, , 2012. This exposure system was developed for crystalline silica particles, however the system would likely work with a wide variety of dry particles.…”
Section: Discussionmentioning
confidence: 99%
“…Research is being conducted which is attempting to accurately predict the outcome of occupational exposure to silica at early stages. For example, a hypothesis is being tested whether a blood gene expression profile can be used as a noninvasive marker capable of predicting organ toxicity in preclinical stages in workers who have occupational exposure risk to airborne silica (Sellamuthu et al, 2011(Sellamuthu et al, , 2012. To aid in this type of research, an automated system that could aerosolize, disperse and carefully control the airborne silica powder within an inhalation exposure chamber was developed.…”
Section: Introductionmentioning
confidence: 99%